2021
DOI: 10.1038/s41427-021-00318-8
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in organic luminescent materials with narrowband emission

Abstract: The International Telecommunication Union announced a new color gamut standard of broadcast service television (BT 2020) for ultra-high-definition TV in 2012. To satisfy the wide-color gamut standard of BT 2020, monochromatic red (R), green (G), and blue (B) emissions require a small full width at half-maximum, which is an important property for improving color purity. Although organic light-emitting diode (OLED) displays are currently one of the main types of display technologies, their broad emission via str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
282
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 320 publications
(294 citation statements)
references
References 118 publications
11
282
0
1
Order By: Relevance
“…into the helicene skeleton to produce thermally activated delayed fluorescence (TADF) is a promising way of improving the exciton utilization and changing the electronic structure. [23][24][25][26][27][28][29][30][31][32][33][34][35][36] For example, Hatakeyama et al reported an ultrapure blue multiple-resonance thermally activated delayed fluorescence (MR-TADF) molecule with rigid hetero [4]-helicene (DABNA-1, Fig. 1a), which exhibits a high PLQY, a large oscillator strength, a small energy difference (DE ST ) between the lowest excited singlet (S 1 ) and triplet (T 1 ) energies, as well as a high device efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…into the helicene skeleton to produce thermally activated delayed fluorescence (TADF) is a promising way of improving the exciton utilization and changing the electronic structure. [23][24][25][26][27][28][29][30][31][32][33][34][35][36] For example, Hatakeyama et al reported an ultrapure blue multiple-resonance thermally activated delayed fluorescence (MR-TADF) molecule with rigid hetero [4]-helicene (DABNA-1, Fig. 1a), which exhibits a high PLQY, a large oscillator strength, a small energy difference (DE ST ) between the lowest excited singlet (S 1 ) and triplet (T 1 ) energies, as well as a high device efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…5 Although the color purity of the original broad EL band can be modified by introducing a color filter and/or an optical microcavity in commercial OLED displays, this inevitably leads to a significant increase in cost and power consumption. 81,90 Thus, the development of efficient TADF emitters with narrowband emissions, especially those having the ability to achieve high color purity that complies with the Commission Internationale de L’Eclairage (CIE) coordinates requirements defined by the broadcasting standards, is highly important.…”
Section: Application Of Pure Organic Rtp and Tadf Emitters In Electro...mentioning
confidence: 99%
“…11 Multiresonant TADF (MR-TADF) compounds are an alternative class of TADF materials that are typically based on p-and n-doped nanographene (Figure S1). 12,13 Because of their rigid structure, these compounds show narrowband emission, typically with full width of half maxima (FWHM) of around 20-30 nm. Thus, MR-TADF emitters show potential to generate the required deep blue emission demanded by industry, and support the development of stable, efficient, pure blue narrowband emitting organic materials that are expected to revolutionize OLED displays.…”
Section: Introductionmentioning
confidence: 99%